An Analysis of Moral Values from The Characters in The Novel ‘Frankenstein’ by Mary Shalley - Byrendra Aprilyandi; Yanti Ismiyati (Universitas Batanghari Jambi, 2019)
Literature is very complex phenomenon because it described about society life, and it is an expression of an author from their creative imaginations. Prose is ordinary language that people use in writing such as poetry, stories, editorials, books, and etcetera. Frankenstein is novel creation Mary Shelley; it was published on March 11, 1818. This novel tells about Doctor Victor Frankenstein as main character Victor Frankenstein wants to create the perfect creature by combining science and magic. Researcher though content analysis is the correct optional to analyze Moral Values on Frankenstein by Mary Shelley. The method that researcher used in this research is qualitative content analysis. Researcher result findings about moral values in the novel Frankenstein by Mary Shelley includes (1) Bravery, (2) Enthusiasm, (3) Kindhearted, (4) Love and Affection, (5) Loyalty, (6) Perseverance, and (7) Sincerity. For the next researcher, are expected by study the moral values in the novel Frankenstein by Mary Shelley can inspire similar advanced research, such as Moral Philosophy in the novel Frankenstein, or the ideology of the author in novel Frankenstein.Keywords: Moral Values, “Frankenstein” novel